The Third Survey on the Activity of Human Milk Banks in Italy and the Impact of the COVID-19 Pandemic - De Nisi, Giuseppe; E. Moro, Guido; Arslanoglu, Sertac; M. Ambruzzi, Amalia; Biasini, Augusto; Profeti, Claudio; Tonetto, Paola; Bertino, Enrico; the members of AIBLUD (Italian Association of Donor Human Milk Banks), and (International Journal of Nutrition, 2022)
Background Growing scientific evidence points to the benefits of human milk for the growth and development of a newborn. Compelling evidence has confirmed the benefits not only for full-term babies but also for preterm infants. Objective This survey was planned by the Italian Ministry of Health together with the Italian Association of Donor Human Milk Banks (AIBLUD) and aimed to evaluate the activity of human milk banks (HMBs) in Italy in the period 2018-2020, analyzing several items and the impact of the COVID-19 pandemic. Methods Following the two surveys performed in 2012 and 2016, a third survey was planned in the year 2021 to evaluate possible changes in the activity of the Human Milk Banks (HMBs) operating in Italy. A questionnaire was sent to all the 41 HMBs officially operating in Italy in the year 2021 with the purpose to obtain national data concerning milk banks activity, number of donors, volume of human milk collected, and other information related to the years 2018, 2019 and 2020. Additional questions related to the impact of the COVID-19 on the activity of HMBs in the year 2020 were included. Therefore the questionnaire proposed in this third survey collected fundamental data on the donation of human milk with the implications related to the COVID-19 pandemic. Results 90% of the banks (37/41) responded to this survey. The collected data confirm the results of the second survey (2016), with a high level of adherence to the Ministerial Guidelines and the AIBLUD recommendations. The application of the principles of the HACCP system continues to improve (89%), while in the last three years there has been a sharp decline in the home collection service for donor human milk (68%). This decline is mainly linked to the interruption of this service due to the limitations imposed by the pandemic. In 2020 (the year of the COVID-19 pandemic) there was a clear reduction in the number of donors with a return to the values ​​of 2016. The volumes of milk collected, and the average duration of donation, however, remained high. The reasons linked to the reduction in the number of donors are described. Conclusion This survey underlines the high quality standard of Italian HMBs and the usefulness of this service for the national health policy. Despite the difficulties due to the COVID-19 pandemic, the Italian HMBs have maintained an efficient and safe service and have guaranteed the collection of satisfactory volumes of donor milk. Lack of information represents the most important barrier to the donation of human milk.
Keywords: Breastfeeding; human milk bank; donor milk; COVID-19; survey